Porous carbon microsphere material, silicon-carbon composite material and preparation method and application of porous carbon microsphere material and silicon-carbon composite material

Porous carbon microspheres are prepared by electrostatic spraying, and combined with supercritical hydrothermal activation and chemical vapor deposition technology, the problem of porous carbon materials easily lead to pore blockage in lithium-ion batteries is solved, and porous carbon microsphere materials with high mesoporosis and excellent electrochemical performance are achieved, which significantly improves the cycle stability and energy density of the battery.

CN119503797AActive Publication Date: 2025-02-25NINGBO SHANSHAN SILICON-BASED MATERIALS CO LTD

Patent Information

Application Number
CN202411760383.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-25
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

Existing porous carbon materials are prone to cause pore blockage in lithium-ion batteries, limiting the depth deposition of silicon source gas, and affecting the cycling stability and energy density of the battery.

Method used

Porous carbon microspheres were prepared by electrostatic spraying, and their pore structure and mechanical strength were optimized through supercritical hydrothermal activation technology. Silicon was further embedded in the porous carbon microspheres through chemical vapor deposition technology to form a silicon-carbon composite material.

Benefits of technology

The prepared porous carbon microsphere material has high mesoporosis, excellent conductivity and mechanical strength, which significantly improves the cycle stability and energy density of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503797A_ABST
    Figure CN119503797A_ABST
Patent Text Reader

Abstract

The invention discloses a porous carbon microsphere material, a silicon-carbon composite material and a preparation method and application thereof, and the preparation method of the porous carbon microsphere material comprises the following steps: S1, mixing a polymer, a solvent and conductive carbon black to obtain a precursor solution; s2, preparing the precursor solution into a carbon microsphere precursor material by adopting an electrostatic spraying method; s3, sequentially carrying out pre-oxidation and heat treatment on the carbon microsphere precursor material to obtain a spherical carbon material; s4, performing supercritical hydrothermal activation on the spherical carbon material, and performing post-treatment to obtain a porous carbon microsphere material; the activation temperature is 300 to 600 DEG C; the activation pressure is 15 to 30 MPa; the activation time is 0.5 to 1 hour. The porous carbon microspheres prepared by the invention have a series of adjustable physical and chemical characteristics, highly developed pore structures, high mesoporosity and better mechanical strength, and can enable lithium ion batteries to have the characteristics of low pole piece expansion rate, high first coulombic efficiency, excellent cycling stability and the like when being further applied to the lithium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a porous carbon microsphere material, a silicon-carbon composite material, and a preparation method and application thereof. Background Art

[0002] In the context of the rapid development of lithium-ion battery technology, the performance of negative electrode materials has become a key factor restricting the improvement of battery energy density. Silicon is considered to be an ideal negative electrode material due to its extremely high theoretical capacity. However, its significant volume expansion during the charge and discharge process can lead to material rupture and poor cycle stability. To solve this problem, porous carbon materials are considered to be an effective way to improve the performance of silicon-based negative electrodes due to their excellent conductivity, chemical stability and adjustable pore structure. Porous carbon can not only serve as a stable buffer framework to adapt to the volume change of silicon, but also provide more active sites and channels, thereby improving the transmission efficiency of electrons and ions. By combining silicon with porous carbon, the stress concentration of silicon particles can be effectively reduced, the crushing of the material can be inhibited, and the structural stability and cycle life of the composite material can be significantly improved. Therefore, the application of porous carbon in silicon-carbon negative electrode materials not only helps to improve the energy density of the battery, but also has important significance for achieving long cycle life lithium-ion batteries. Future research will continue to optimize the pore structure and preparation method of porous carbon to further improve the comprehensive performance of silicon-carbon negative electrodes and meet the growing demand for high energy density batteries.

[0003] Chinese patent CN118206115B discloses a high-performance asphalt-based porous carbon material and a preparation method thereof, wherein a precursor is prepared by mixing coal tar and carbon nanotubes, followed by pretreatment, crushing, adding graphene and drying, preoxidation treatment, and carbonization and activation treatment to obtain the final product. Although this method solves the problem of incomplete asphalt preoxidation and improves the carbonization yield, the prepared porous carbon material has a high micropore volume ratio, which is easy to cause pore blockage and is not conducive to the deep deposition of silicon source gas during chemical vapor deposition. Chinese patent CN116314734A discloses a preparation method, silicon-carbon composite material and its application. The method includes steam activation and CO2 activation of graphite paper to prepare a modified graphite paper material, and then in a microwave reaction chamber, silane gas and carbon source gas are introduced under microwave action to obtain a silicon-carbon composite material. This preparation method does not use a catalyst, avoiding the problem of impurities caused by the introduction of a catalyst. However, due to the morphology and structure of the activated precursor, the resulting activated material is not sufficiently isotropic. This structural characteristic limits the material's performance in inhibiting the volume expansion of silicon-based materials during charging and discharging, and may cause the material to pulverize during the cycle process, affecting the battery's cycle stability and service life. Summary of the invention

[0004] The present invention aims to solve the problems existing in the above schemes and provides a porous carbon microsphere material, a silicon-carbon composite material and a preparation method and application thereof. The porous carbon microspheres prepared by the present invention have a series of adjustable physical and chemical properties, a highly developed pore structure, a high mesoporosity and good mechanical strength. When further applied to lithium-ion batteries, they can have the characteristics of low pole piece expansion rate, high first coulomb efficiency and excellent cycle stability.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] The present invention provides a method for preparing porous carbon microspheres, which comprises the following steps:

[0007] S1: mixing a polymer, a solvent and conductive carbon black to obtain a precursor solution;

[0008] S2: preparing the precursor solution into a carbon microsphere precursor material by an electrostatic spray method;

[0009] S3: pre-oxidizing and heat-treating the carbon microsphere precursor material in sequence to obtain a spherical carbon material;

[0010] S4: subjecting the spherical carbon material to supercritical hydrothermal activation and post-treatment to obtain a porous carbon microsphere material;

[0011] The activation temperature is 300-600° C.; the activation pressure is 15-30 MPa; and the activation time is 0.5-1 h.

[0012] In the present invention, in step S1, the polymer may include polymer A and polymer B; the polymer A and the polymer B are different polymers.

[0013] In some preferred embodiments, in step S1, the polymer A is one of polystyrene, polyacrylonitrile, polydopamine and poly(aniline-pyrrole) copolymer, for example, polystyrene.

[0014] In the above solution, the weight average molecular weight of the polystyrene is preferably 100000-200000 g / mol, more preferably 130000-170000 g / mol, for example 150000 g / mol.

[0015] In some preferred embodiments, in step S1, the polymer B is polyvinyl pyrrolidone.

[0016] In the above scheme, the weight average molecular weight of the polyvinyl pyrrolidone is preferably 40000-100000 g / mol, more preferably 40000-70000 g / mol, for example 60000 g / mol.

[0017] In some preferred embodiments, in step S1, the mass ratio of the polymer A, the polymer B and the conductive carbon black is (4-9):(4-9):(2-5), preferably: (5-7):(5-7):(2-4), for example: 2:2:1 or 5:5:2.

[0018] In some preferred embodiments, in step S1, the solvent is N,N-dimethylformamide.

[0019] In some preferred embodiments, in step S1, the conductive carbon black is one of Ketjen black, acetylene black and Super P.

[0020] In some preferred embodiments, in step S1, the concentration of the polymer solution is 5-12 wt%, preferably 6-10 wt%, for example 6 wt% or 8 wt%; the concentration of the polymer solution is the percentage of the total mass of the polymer to the mass of the solvent.

[0021] In some preferred embodiments, in step S1, the mixing operation is to dissolve the polymer in a solvent, form a homogeneous polymer solution through magnetic stirring, then add the conductive carbon black to the polymer solution, and obtain a precursor solution through ultrasonic dispersion.

[0022] In the above scheme, the rotation speed of the magnetic stirring is preferably 200-350 rpm, for example, 300 rpm; the time of the magnetic stirring is preferably 2-6 h, for example, 4 h.

[0023] In the above scheme, the ultrasonic dispersion time is preferably 1 to 2 h.

[0024] In some more preferred embodiments, in step S1, the mixing operation is to dissolve polystyrene and polyvinyl pyrrolidone in N,N-dimethylformamide, form a homogeneous polymer solution after magnetic stirring, then add conductive carbon black to the polymer solution, and obtain a precursor solution after ultrasonic dispersion.

[0025] In some preferred embodiments, in step S2, the operation of the electrostatic spray method is: inject the precursor solution obtained in step S1 into a syringe, then fix the syringe on a microinjection pump, connect the positive electrode of the high-voltage power supply to the root of the syringe needle, connect the receiving electrode to the ground wire, place it perpendicular to the radial direction of the syringe and directly below the syringe, adjust the equipment parameters for electrostatic spraying, and obtain a carbon microsphere precursor.

[0026] In the above scheme, in step S2, the flow rate of the microinjection pump is preferably 0.5~1.5 mL / h, for example: 0.6 mL / h or 0.8 mL / h; the voltage of the high-voltage power supply is preferably 15~30 kV, for example: 20 kV or 22 kV; the receiving distance from the tip of the syringe to the receiving plate is preferably 12~18 cm, for example: 16 cm.

[0027] In the present invention, in step S2, the operating environment temperature of the electrostatic spraying method can be 20-30° C., and the ambient humidity can be 35%-55%.

[0028] In some preferred embodiments, in step S3, the pre-oxidation operation is to dry the carbon microsphere precursor material obtained in step S2, transfer it to a muffle furnace, and heat it in an air atmosphere.

[0029] In the above scheme, in step S3, the drying temperature is preferably 90-160° C., for example, 150° C., and the drying time is preferably 18-36 h, for example, 24 h. The non-volatile solvent in the carbon microsphere precursor material is removed by drying.

[0030] In some preferred embodiments, in step S3, the heating rate of the pre-oxidation is 1-4°C / min, for example, 2°C / min.

[0031] In some preferred embodiments, in step S3, the pre-oxidation temperature is 150-280°C, preferably 170-250°C.

[0032] In some preferred embodiments, in step S3, the pre-oxidation time is 2 to 6 hours, preferably 2 to 4 hours. The pre-oxidation time is the time of constant temperature insulation after the temperature is raised to the pre-oxidation temperature.

[0033] In the present invention, the cross-linking degree of the carbon microsphere precursor material is increased during the pre-oxidation treatment process, thereby slowing down the rapid removal of small molecules during the subsequent high-temperature carbonization process and improving the carbon yield of the target product.

[0034] In some preferred embodiments, in step S3, the heat treatment is performed in an inert atmosphere, and the inert atmosphere is at least one or two of nitrogen and argon, for example, nitrogen.

[0035] In some preferred embodiments, in step S3, the heat treatment is performed in a tubular atmosphere furnace.

[0036] In some preferred embodiments, in step S3, the heating rate of the heat treatment is 5-7°C / min.

[0037] In some preferred embodiments, in step S3, the temperature of the heat treatment is 500-1200°C, preferably 600-1000°C, for example 900°C.

[0038] In some preferred embodiments, in step S3, the heat treatment time is 1 to 3 hours, for example, 2 hours. The heat treatment time is the time of constant temperature insulation after the temperature is raised to the heat treatment temperature.

[0039] In the present invention, in step S3, the particle size of the spherical carbon material may be D50<10 μm, D90<20 μm.

[0040] In some preferred embodiments, in step S4, the operation of supercritical hydrothermal activation is to transfer the spherical carbon material obtained in step S3 into a supercritical water activation reactor, first adjust the preheater to a specified temperature, and then perform hydrothermal activation at the set temperature and pressure in the supercritical water activation reactor to obtain an activated material.

[0041] In some preferred embodiments, in step S4, the water used for the supercritical hydrothermal activation is one of deionized water, ultrapure water and distilled water, preferably deionized water.

[0042] In some preferred embodiments, in step S4, the preheating temperature of the supercritical hydrothermal activation is 100-200°C, for example, 150°C.

[0043] In some preferred embodiments, in step S4, the pressure increase rate of the supercritical hydrothermal activation is 0.8-1.2 MPa / min, for example: 1 MPa / min.

[0044] In some preferred embodiments, in step S4, the pressure of the supercritical hydrothermal activation is 15-30 Mpa, for example, 20 Mpa or 25 Mpa.

[0045] In some preferred embodiments, in step S4, the heating rate of the supercritical hydrothermal activation is 25-35°C / min, for example, 30°C / min.

[0046] In some preferred embodiments, in step S4, the temperature of the supercritical hydrothermal activation is 300-600°C, for example, 500°C.

[0047] In some preferred embodiments, in step S4, the supercritical hydrothermal activation time is 30 to 60 minutes, for example, 45 minutes. The supercritical hydrothermal activation time is the time of constant temperature insulation after the temperature reaches the supercritical hydrothermal activation temperature.

[0048] In some preferred embodiments, in step S4, the post-treatment operation is to wash and dry the activated material to obtain a porous carbon microsphere material.

[0049] In some more preferred embodiments, in step S4, the washing operation is acid washing, alkali washing and water washing in sequence.

[0050] In the above scheme, in step S4, the acid solution used in the pickling operation is preferably one of hydrochloric acid, sulfuric acid and nitric acid, for example, hydrochloric acid.

[0051] In the above scheme, in step S4, the concentration of the acid solution used in the pickling operation is preferably 5-30%, more preferably 10-20%. The concentration of the acid solution is the percentage of the mass of the acid substance to the mass of the acid solution.

[0052] In the present invention, the pickling process is mainly to deash the material after supercritical hydrothermal activation and further create pores to improve the adsorption performance of the product. However, excessive pickling will cause the pore structure to be destroyed, affecting the mechanical properties and cycle life of the product.

[0053] In the above scheme, in step S4, the alkaline solution used in the alkaline washing operation is preferably one of sodium hydroxide, potassium hydroxide and potassium carbonate, for example, sodium hydroxide.

[0054] In the above scheme, in step S4, the concentration of the alkaline solution used in the alkaline washing operation is preferably 3-10%, for example, 5%. The concentration of the alkaline solution is the percentage of the mass of the alkaline substance to the mass of the alkaline solution.

[0055] In the present invention, the alkaline washing process is mainly to adjust the pH value of the target product.

[0056] In the above scheme, in step S4, the water washing operation is preferably performed by adjusting the pH value of the object to be washed to 6-8.

[0057] In the above scheme, in step S4, the water washing operation is preferably performed using pure water.

[0058] In some more preferred embodiments, in step S4, the drying operation is performed under one of air, nitrogen and argon atmospheres, for example, air.

[0059] In some more preferred embodiments, in step S4, the drying temperature is preferably 100-170°C, more preferably 100-150°C, for example 130°C.

[0060] In some more preferred embodiments, in step S4, the drying time is preferably 2 to 5 h, more preferably 2 to 4 h.

[0061] In the present invention, the carbonization yield of the porous carbon microspheres can be 45% to 60%, preferably 45% to 55%. The carbonization yield is the percentage of the mass of the spherical carbon material obtained in step S3 to the mass of the carbon microsphere precursor material obtained in step S2.

[0062] The present invention provides a porous carbon microsphere, which is prepared by the method for preparing the porous carbon microsphere as described above.

[0063] The present invention provides a porous carbon microsphere, wherein the average pore size of the porous carbon microsphere is 2-6 nm; the mesoporosity of the porous carbon microsphere is 40%-80%; the mesopore volume of the porous carbon microsphere is 0.2-0.8 cm 3 / g; the micropore volume of the porous carbon microspheres is 0.3~0.6 cm 3 / g; the compressive strength of the porous carbon microspheres is 4.8~8.0 Gpa.

[0064] In the present invention, the mesoporosity is the percentage of the mesopore volume of the porous carbon microspheres to the total pore volume; the total pore volume is the sum of the micropore volume and the mesopore volume.

[0065] In some preferred embodiments, the average pore size of the porous carbon microspheres is 2-4 nm; the mesoporosity of the porous carbon microspheres is 48%-65%; the mesopore volume of the porous carbon microspheres is 0.3-0.6 cm 3 / g; the micropore volume of the porous carbon microspheres is 0.3~0.5 cm 3 / g; the compressive strength of the porous carbon microspheres is 5.2~7.0 Gpa.

[0066] In some preferred embodiments, the specific surface area of ​​the porous carbon microspheres is 700-1500 m 2 / g, preferably 1000~1400 m 2 / g; the total pore volume of the porous carbon microspheres is 0.4~1.3 cm 3 / g, preferably 0.7~1.0 cm 3 / g;

[0067] In some preferred embodiments, the D50 of the porous carbon microspheres is less than 9 μm, preferably 6.7-8.3 μm; the D90 of the porous carbon microspheres is less than 17 μm, preferably 14.2-16.8 μm.

[0068] The present invention provides a silicon-carbon composite material, which comprises the porous carbon microspheres and silicon, wherein the silicon is enriched inside the pores of the porous carbon microspheres.

[0069] In some preferred embodiments, the silicon content in the silicon-carbon composite material is 45% to 60%. The silicon content is the mass percentage of the silicon-carbon composite material.

[0070] In the present invention, the silicon-carbon composite material can be prepared by conventional methods in the art, and preferably, the silicon is deposited in the porous carbon microspheres by chemical vapor deposition.

[0071] The present invention provides an application of the silicon-carbon composite material as an electrode material in a lithium-ion battery.

[0072] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0073] The reagents and raw materials used in the present invention are commercially available.

[0074] The positive and progressive effects of the present invention are:

[0075] (1) The porous carbon microsphere material prepared by the present invention has a series of adjustable physical and chemical properties, such as particle size distribution, pore size, pore volume, mesoporosity and specific surface area, etc. The optimization of these properties further improves the mechanical strength and subsequent electrochemical performance of the material. By precisely controlling the preparation process, the porous carbon microspheres of the present invention not only meet the specific needs of high-performance battery materials in diversified applications, but also provide new ideas and solutions for the development of related application fields.

[0076] (2) The present invention uses a supercritical water activation process to successfully prepare porous carbon microspheres with a highly developed pore structure and high mesoporosity. This porous structure with high mesoporosity not only enhances the conductivity of the material, but also improves the permeability of the electrolyte, providing an effective channel for the rapid transmission of lithium ions and providing an efficient carrier for the silicon-carbon negative electrode material of lithium-ion batteries. In addition, this porous structure also helps to buffer the volume expansion of silicon during the charge and discharge process, thereby improving the cycle stability of the battery.

[0077] (3) The porous carbon microsphere material prepared by the present invention provides the material with the necessary mechanical properties, enabling it to maintain structural integrity during the battery charging and discharging process. This optimization of mechanical strength helps to reduce the wear and breakage of the material, extend the service life of the battery, and improve the overall reliability of the battery.

[0078] (4) The carbon microsphere precursor prepared by the electrostatic spraying technology of the present invention has a uniform size distribution, which ensures the consistency and charge-discharge performance of the material in battery applications. In addition, the introduction of conductive carbon black is beneficial to improving the conductivity of the carbon matrix.

[0079] (5) After the porous carbon microspheres of the present invention are embedded in silicon material by chemical vapor deposition technology, the prepared silicon-carbon composite material exhibits low electrode expansion rate and high first coulomb efficiency. These improvements in electrochemical properties directly enhance the cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0080] Figure 1 This is a SEM image of the porous carbon microspheres prepared in Example 1 of the present invention.

[0081] Figure 2 The nitrogen adsorption-desorption isotherms of the porous carbon microspheres prepared in Example 1 and Comparative Example 2 of the present invention are shown.

[0082] Figure 3 The pore size distribution diagram of the porous carbon microspheres prepared in Example 1 and Comparative Example 2 of the present invention.

[0083] Figure 4 This is a schematic diagram of the structure of the supercritical water activation reactor in Example 1 of the present invention.

[0084] Description of reference numerals:

[0085] Gas cylinder 1

[0086] Water Tower 2

[0087] Gas flow meter 3

[0088] Piston pump 4

[0089] High pressure valve 5

[0090] Pressure indicator 6

[0091] Preheater 7

[0092] Reactor 8

[0093] Activation furnace 9

[0094] Heat exchanger 10

[0095] Back pressure regulator 11

[0096] Gas-liquid separator 12. DETAILED DESCRIPTION

[0097] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0098] The electrostatic spray environment in the following examples and comparative examples is: temperature 25±5°C, humidity 45%±10%; polystyrene weight average molecular weight is 150,000 g / mol, purchased from Shanghai Hongshun Biotechnology Co., Ltd.; polyvinyl pyrrolidone weight average molecular weight is 60,000 g / mol, purchased from Guangzhou Yuemei Chemical Co., Ltd.

[0099] Example 1

[0100] S1: Dissolve 0.8 g polystyrene and 0.8 g polyvinyl pyrrolidone in 19 mL N,N-dimethylformamide (density of N,N-dimethylformamide is 0.948 g / cm 3 ) was prepared into a solution with a concentration of 8 wt%, and a homogeneous polymer solution was obtained after magnetic stirring at a speed of 300 rpm at room temperature for 4 h, and then 0.4 g of Ketjen black was added thereto and ultrasonically dispersed for 1 h to obtain a uniformly dispersed precursor solution;

[0101] S2: Inject the precursor solution prepared in step S1 into a 20 mL syringe, then fix the syringe on a microinjection pump, connect the positive electrode of the high-voltage power supply to the root of the syringe needle, connect the receiving electrode to the ground wire, place it perpendicular to the radial direction of the syringe and directly below the syringe, adjust the equipment parameters for electrostatic spraying, set the flow rate to 0.8 mL / h, apply a voltage of 20 kV, and the receiving distance to 16 cm to obtain a carbon microsphere precursor material;

[0102] S3: pre-oxidizing the carbon microsphere precursor material obtained in step S2, i.e., drying it in a constant temperature drying oven at 150°C for 24 h, then transferring it to a muffle furnace, heating it to 250°C at a heating rate of 2°C / min in an air atmosphere and keeping the temperature constant for 4 h; then heat treating it, i.e., heating it to 900°C at a heating rate of 5°C / min in a tubular atmosphere furnace in a nitrogen atmosphere and keeping the temperature constant for 2 h, to obtain a spherical carbon material;

[0103] S4: The spherical carbon material obtained in step S3 is transferred into a supercritical water activation reactor, and the preheater temperature is adjusted to 150°C to ensure that the deionized water is in a water vapor state when passing through the material. Subsequently, the plunger pump is turned on and the reaction pressure is set to 25MPa. After the pressure is increased to the set pressure at a pressure increase rate of 1 MPa / min, the reactor is heated to 500°C at a temperature increase rate of 30°C / min and maintained at a constant temperature and pressure for 45 min to obtain an activated material; the activated material obtained is washed with 10% hydrochloric acid, 5% sodium hydroxide, and pure water in turn, and treated in a drying oven at a constant temperature of 130°C for 2 h to obtain a porous carbon microsphere material.

[0104] Example 2

[0105] S1: Dissolve 0.55 g polystyrene and 0.55 g polyvinyl pyrrolidone in 18 mL N,N-dimethylformamide (density of N,N-dimethylformamide is 0.948 g / cm 3 ) was prepared into a solution with a concentration of 6 wt%, and magnetically stirred at 300 rpm for 4 h at room temperature to obtain a homogeneous polymer solution, to which 0.22 g of Ketjen black was then added and ultrasonically dispersed for 1 h to obtain a uniformly dispersed precursor solution. Other conditions were the same as those in Example 1.

[0106] Example 3

[0107] In step S2, the microinjection pump flow rate is 0.6 mL / h, and the applied voltage is 22 kV. Other conditions are the same as those in Example 1.

[0108] Example 4

[0109] In step S4, the activation pressure is set to 20 MPa. Other conditions are the same as those in Example 1.

[0110] Example 5

[0111] In step S4, the activation time is 30 min. Other conditions are the same as those in Example 1.

[0112] Comparative Example 1

[0113] No pre-oxidation treatment is performed in step S3, and the specific implementation process is as follows:

[0114] The carbon microsphere precursor material obtained in step S2 of Example 1 was dried in a constant temperature drying oven at 150°C for 24 h, and then transferred to a tubular atmosphere furnace in a nitrogen atmosphere, and heated to 900°C at a heating rate of 5°C / min and kept at this temperature for 2 h to obtain a spherical carbon material. Other conditions were the same as those in Example 1.

[0115] Comparative Example 2

[0116] In step S4, supercritical water thermal activation is not performed, and the specific implementation process is as follows:

[0117] The spherical carbon material obtained in step S3 of Example 1 was transferred into the reactor, the preheater temperature was adjusted to 150°C, the deionized water was ensured to be in a water vapor state when passing through the material, the plunger pump was adjusted to stabilize the water vapor flow rate at 2 L / min, and the reactor was heated to 800°C at a heating rate of 10°C / min and kept at a constant temperature for 45 min. Other conditions were the same as in Example 1.

[0118] Comparative Example 3

[0119] The activation temperature in step S4 is set to 700° C. Other conditions are the same as those in Example 1.

[0120] Effect Example 1

[0121] Characterization of properties of porous carbon microspheres

[0122] (1) Test method

[0123] A. The specific surface area, total pore volume, average pore size, mesoporosity, mesopore volume, micropore volume, and nitrogen adsorption-desorption isotherms of the porous carbon microsphere materials prepared in the above embodiments and comparative examples were characterized using an Autosorb iQ-3 fully automatic specific surface area and pore size analyzer.

[0124] Before testing, the sample needs to be degassed to remove low-volatile substances such as water. The degassing temperature is 250°C and the degassing time is 720 min. Then the sample tube is installed on the analysis station and placed in a cold trap Dewar flask at liquid nitrogen temperature (77 K) to measure its nitrogen adsorption and desorption isotherm. The test pressure range is 10 -7 ~1 bar. The specific surface area of ​​the sample was determined by the BET (Brunauer-Emmett-Teller) method, with the selection point range (P / P0) being 0.004~0.3; the micropore specific surface area and micropore volume of the sample were determined by the t-plot method, with the selection point range being 0.2~0.4; the value corresponding to the relative pressure point of 0.99 was its total pore volume; the pore size distribution of the sample was analyzed by non-local density functional theory (NLDFT).

[0125] B. Carbonization yield

[0126] Carbonization yield = mass (g) of the spherical carbon material obtained in step S3 / mass (g) of the carbon microsphere precursor material obtained in step S2.

[0127] C. Compressive strength

[0128] (a) Test standard: GB / T 43091-2023

[0129] (b) Test instrument: FT-2000A

[0130] (c) Test steps:

[0131] The compressive strength test was performed on the porous carbon microsphere materials prepared in each embodiment and comparative example. According to the requirements in the test standard, the test environment temperature was 25±3° C., the relative humidity was not greater than 60%, and there was no vibration or convection air influence during the test.

[0132] Place the sample to be tested on the test platform, use a microscope to find individual particles within the field of view of the plane indenter, and use the plane indenter to apply pressure to the particles. The powder particles deform as the pressure increases until they are crushed. The test force when the powder is crushed is the crushing force F of the particles. ykThe force-bearing area of ​​the particles is calculated according to the particle size d of the powder particles, and then the compressive strength of the powder particles pcs is calculated. The number of test particles is not less than 5, and the number of test particles can also be selected according to actual needs.

[0133] Calculation of powder compressive strength:

[0134]

[0135] In the formula, p cs is the compressive strength, in MPa; α is the calculation coefficient, which is 2.48; F yk is the crushing force, in mN; d is the particle size, in μm.

[0136] D. Surface morphology

[0137] The present invention adopts a German Zeiss Sigma 300 field emission scanning electron microscope to test the surface morphology of the prepared porous carbon microsphere material.

[0138] Test steps: Take a small amount of sample and attach it to the sample stage with conductive glue. After spraying gold on the sample for 45 seconds, put it into the vacuum chamber of the scanning electron microscope for surface morphology observation.

[0139] Test conditions: Acceleration voltage 5.0 kV, electron imaging resolution: 1.6 nm (1 kV), 1.0 nm (15 kV)

[0140] (2) Test results

[0141] Table 1

[0142]

[0143] Figure 1 This is a SEM image of the porous carbon microspheres prepared in Example 1 of the present invention; Figure 2 The nitrogen adsorption-desorption isotherms of the porous carbon microspheres prepared in Example 1 and Comparative Example 2 of the present invention; Figure 3 The pore size distribution diagram of the porous carbon microspheres prepared in Example 1 and Comparative Example 2 of the present invention. According to the IUPAC classification standard, Figure 2 The adsorption isotherms of Example 1 and Comparative Example 2 show a typical IV type curve and have an obvious H3 type hysteresis loop, that is, there are both micropores and mesopores. The difference between the two is that the total adsorption amount of Comparative Example 2 is greater than that of Example 1, indicating that the specific surface area of ​​Comparative Example 2 is larger. Figure 3It can be seen that the difference in pore structure between Example 1 and Comparative Example 2 is further revealed by the pore size distribution calculated by the NLDFT method. In Example 1, the pore size distribution is relatively wide, and the pores are mainly mesopores between 2-3 nm and 3.5-4.5 nm, while the pores of Comparative Example 2 are mainly micropores <2 nm and some mesopores between 4.5-5 nm. Figure 2 This is also confirmed by the hysteresis loop of the adsorption-desorption curve.

[0144] Combined with the data in Table 1, it can be seen that the porous carbon microsphere material prepared by the technical solution of the present invention has the characteristics of uniform size, high mesoporosity and high particle strength. By comparing Examples 1-5 and Comparative Example 2, it can be found that the material prepared by supercritical water activation technology has higher particle strength and mesoporosity. Combined with Comparative Example 3, it can be seen that although the porous carbon microspheres over-activated by supercritical water have a higher mesoporosity, the carbon matrix that plays a supporting role inside has been over-activated, resulting in a lower compressive strength; at the same time, the average pore size of the porous carbon microsphere materials obtained in Examples 1-5 is higher than that of Comparative Example 2, and smaller than that of Comparative Example 3.

[0145] In addition, by comparing Examples 1-5 and Comparative Example 1, it can be found that the carbonization yield and compressive strength of the carbon material that has undergone pre-oxidation treatment are significantly higher than those of the carbon material that has not undergone pre-oxidation treatment. This is because during the pre-oxidation process, the introduction of oxygen from the air atmosphere can enhance the cross-linking between resin molecules and inhibit the conversion of carbon in the molecules into small molecular carbon-containing gases. The increase in carbon yield helps to build a more continuous and efficient conductive network, thereby improving structural stability.

[0146] Effect Example 2

[0147] Characterization of properties of silicon-carbon composites

[0148] (1) Test method

[0149] Silane Vapor Phase Chemical Deposition

[0150] The porous carbon microspheres prepared in each embodiment and comparative example are subjected to silicon source gas vapor deposition to prepare a silicon-carbon composite material, and the specific steps are as follows:

[0151] A mixture of monosilane and nitrogen was introduced into a positive pressure fluidized bed reactor at 120 kPa, with a monosilane gas flow rate of 10 L / min and a nitrogen gas flow rate of 25 L / min. The monosilane in the mixed gas reacted with the porous carbon microspheres at 650°C for 1.5 h. After the deposition reaction was completed, the introduction of monosilane was stopped, and only nitrogen was introduced to complete the gas replacement in the reactor. Subsequently, air was introduced and heated at 100°C for 0.5 h for surface passivation to obtain a silicon-carbon composite material.

[0152] The calculation method of silicon content in the silicon-carbon composite material prepared above is as follows:

[0153] Silicon content = (mass after passivation treatment m1 - mass before deposition reaction m0) / mass after passivation treatment m1.

[0154] (2) Test results

[0155] The test results are shown in Table 2.

[0156] Table 2

[0157]

[0158] As can be seen from Table 2 above, by comparing Examples 1-5 with Comparative Example 2, it can be found that the corresponding silicon deposition content of the product obtained by supercritical water activation technology is also higher than that of Comparative Example 2. This is because the average pore size of the product that is not activated by supercritical water is smaller, and the pores are easily blocked after deposition, and the internal space cannot continue to deposit, resulting in a lower silicon content, and its corresponding electrochemical performance will also be weakened. By comparing Examples 1-5 with Comparative Example 3, it can be found that when the average pore size of the product obtained by supercritical water activation technology is larger and the specific surface area is smaller at the temperature specified by the present invention, the silicon content that can be deposited is less, which will also have an adverse effect on its corresponding electrochemical performance.

[0159] As for comparative example 1, since the carbon material without pre-oxidation forms a certain degree of closed pores after carbonization (the internal pores have no channels connected to the outer surface, forming an independent pore structure), the carbonization yield is reduced. After activation, some of the closed pores are opened, and these opened closed pores contribute to the increase of specific surface area and pore volume. However, the formation of closed pores is not conducive to the mechanical properties of carbon materials, and it is more likely to collapse under the same pressure. In addition, during the charge and discharge process, the lithium ions embedded in the opened closed pores are confined to the nanospace and fail to escape in time, forming "dead lithium". Therefore, its subsequent electrochemical performance is also poor.

[0160] Effect Example 3

[0161] Electrochemical performance test

[0162] (1) Test method

[0163] The silicon-carbon composite material obtained by silane deposition in each embodiment and comparative example was mixed with SFG-6 and LA132 to prepare a slurry, and the mixing ratio was 75:15:10. The mixed slurry was coated on a copper foil, and after drying and rolling, it was cut into a disc with a diameter of 13.5 mm as a negative electrode, which was assembled with a lithium sheet, an electrolyte, a polypropylene diaphragm, a positive electrode shell, and a negative electrode shell into a CR2430 button battery. The electrolyte is prepared with lithium hexafluorophosphate as a solute, ethylene carbonate and diethyl carbonate as solvents, wherein the volume ratio of ethylene carbonate to diethyl carbonate is 1:1, and the concentration of lithium hexafluorophosphate is 0.8 mol / L. The button battery was subjected to a constant current charge and discharge test at 0.1 C using a blue battery test system to test the capacity, first effect, and capacity retention rate after 100 and 500 cycles.

[0164] (2) Test results

[0165] The test results are shown in Table 3.

[0166] Table 3

[0167]

[0168] As can be seen from Table 3, the silicon-carbon composite material prepared by the present invention has excellent reversible specific capacity, first coulomb efficiency, and capacity retention rate after 100 cycles and 500 cycles. The reversible specific capacity and capacity retention rate after 500 cycles of Examples 1-5 are higher than those of Comparative Examples 1-3. In combination with the mechanical properties of the materials, Example 1 and Comparative Example 2 are compared, and the capacity retention rates of the two after 100 cycles are relatively close, but after 500 cycles, the capacity retention rate of the silicon-carbon composite material obtained by water vapor activation in Comparative Example 2 shows a large attenuation, which shows that the silicon-carbon composite material prepared by the present invention has excellent mechanical properties and electrochemical properties.

Claims

1. A method for preparing porous carbon microspheres, characterized in that: It includes the following steps: S1: mixing a polymer, a solvent and conductive carbon black to obtain a precursor solution; S2: preparing the precursor solution into a carbon microsphere precursor material by an electrostatic spray method; S3: pre-oxidizing and heat-treating the carbon microsphere precursor material in sequence to obtain a spherical carbon material; S4: subjecting the spherical carbon material to supercritical hydrothermal activation and post-treatment to obtain a porous carbon microsphere material; The activation temperature is 300-600° C.; the activation pressure is 15-30 MPa; and the activation time is 0.5-1 h.

2. The method for preparing porous carbon microspheres according to claim 1, characterized in that: It meets one or more of the following conditions: (1) In step S1, the polymer includes polymer A and polymer B; the polymer A and the polymer B are different polymers; Preferably, in step S1, the polymer A is one of polystyrene, polyacrylonitrile, polydopamine and poly(aniline-pyrrole) copolymer, for example: polystyrene; Wherein, the weight average molecular weight of the polystyrene is preferably 100000-200000 g / mol, more preferably 130000-170000 g / mol, for example: 150000 g / mol; Preferably, in step S1, the polymer B is polyvinyl pyrrolidone; Wherein, the weight average molecular weight of the polyvinyl pyrrolidone is preferably 40000-100000 g / mol, more preferably 40000-70000 g / mol, for example: 60000 g / mol; Preferably, in step S1, the mass ratio of the polymer A, the polymer B and the conductive carbon black is (4-9): (4-9): (2-5), more preferably: (5-7): (5-7): (2-4), for example: 2:2:1 or 5:5:2; (2) In step S1, the solvent is N,N-dimethylformamide; (3) In step S1, the conductive carbon black is one of Ketjen black, acetylene black and Super P; (4) In step S1, the concentration of the polymer solution is 5-12 wt%, preferably 6-10 wt%, for example 6 wt% or 8 wt%; (5) In step S1, the mixing operation is to dissolve the polymer in a solvent, form a homogeneous polymer solution after magnetic stirring, then add the conductive carbon black to the polymer solution, and obtain a precursor solution after ultrasonic dispersion; The rotation speed of the magnetic stirring is preferably 200-350 rpm, for example, 300 rpm; the time of the magnetic stirring is preferably 2-6 h, for example, 4 h; Wherein, the ultrasonic dispersion time is preferably 1 to 2 h; (6) In step S1, the mixing operation is to dissolve polystyrene and polyvinyl pyrrolidone in N,N-dimethylformamide, and form a homogeneous polymer solution after magnetic stirring, and then add conductive carbon black to the polymer solution, and obtain a precursor solution after ultrasonic dispersion.

3. The method for preparing porous carbon microspheres according to claim 1, characterized in that: It meets one or more of the following conditions: (1) In step S2, the operation of the electrostatic spray method is as follows: inject the precursor solution obtained in step S1 into a syringe, then fix the syringe on a micro-injection pump, connect the positive electrode of the high-voltage power supply to the root of the syringe needle, connect the receiving plate to the ground wire, place it perpendicular to the radial direction of the syringe and directly below the syringe, adjust the equipment parameters for electrostatic spraying, and obtain a carbon microsphere precursor; Wherein, in step S2, the flow rate of the microinjection pump is preferably 0.5-1.5 mL / h, for example: 0.6 mL / h or 0.8 mL / h; the voltage of the high-voltage power supply is preferably 15-30 kV, for example: 20 kV or 22 kV; the receiving distance from the tip of the syringe to the receiving plate is preferably 12-18 cm, for example: 16 cm; (2) In step S2, the operating environment temperature of the electrostatic spraying method is 20-30°C and the ambient humidity is 35%-55%.

4. The method for preparing porous carbon microspheres according to claim 1, characterized in that: It meets one or more of the following conditions: (1) In step S3, the pre-oxidation operation is to dry the carbon microsphere precursor material obtained in step S2, transfer it to a muffle furnace, and heat it in an air atmosphere; Wherein, in step S3, the drying temperature is preferably 90-160°C, for example, 150°C; the drying time is preferably 18-36 h, for example, 24 h; (2) In step S3, the pre-oxidation heating rate is 1-4°C / min, for example, 2°C / min; (3) In step S3, the pre-oxidation temperature is 150-280°C, preferably 170-250°C; (4) In step S3, the pre-oxidation time is 2 to 6 hours, preferably 2 to 4 hours; (5) In step S3, the heat treatment is performed in an inert atmosphere, wherein the inert atmosphere is at least one or two of nitrogen and argon, for example, nitrogen; (6) In step S3, the heat treatment is performed in a tubular atmosphere furnace; (7) In step S3, the heating rate of the heat treatment is 5-7°C / min; (8) In step S3, the temperature of the heat treatment is 500-1200°C, preferably 600-1000°C, for example 900°C; (9) In step S3, the heat treatment time is 1 to 3 hours, for example, 2 hours; (10) The particle size of the spherical carbon material is D50<10 μm, D90<20 μm.

5. The method for preparing porous carbon microspheres according to claim 1, characterized in that: It meets one or more of the following conditions: (1) In step S4, the operation of supercritical water thermal activation is to transfer the spherical carbon material obtained in step S3 into a supercritical water activation reactor, first adjust the preheater to a specified temperature, and then perform hydrothermal activation at the set temperature and pressure of the supercritical water activation reactor to obtain an activated material; (2) In step S4, the water used for the supercritical water thermal activation is one of deionized water, ultrapure water and distilled water, preferably deionized water; (3) In step S4, the preheating temperature of the supercritical hydrothermal activation is 100-200°C, for example, 150°C; (4) In step S4, the pressure increase rate of the supercritical water thermal activation is 0.8-1.2 MPa / min, for example: 1 MPa / min; (5) In step S4, the pressure of the supercritical water thermal activation is 15-30 Mpa, for example, 20 Mpa or 25 Mpa; (6) In step S4, the heating rate of the supercritical hydrothermal activation is 25-35°C / min, for example, 30°C / min; (7) In step S4, the temperature of the supercritical water thermal activation is 300-600°C, for example, 500°C; (8) In step S4, the supercritical hydrothermal activation time is 30 to 60 min, for example, 45 min; (9) In step S4, the post-treatment operation is to wash and dry the activated material to obtain a porous carbon microsphere material; Preferably, in step S4, the washing operation is acid washing, alkali washing and water washing in sequence; Wherein, in step S4, the acid solution used in the pickling operation is preferably one of hydrochloric acid, sulfuric acid and nitric acid, for example: hydrochloric acid; Wherein, in step S4, the concentration of the acid solution used in the pickling operation is preferably 5-30%, more preferably 10-20%; Wherein, in step S4, the alkaline solution used in the alkaline washing operation is preferably one of sodium hydroxide, potassium hydroxide and potassium carbonate, for example: sodium hydroxide; Wherein, in step S4, the concentration of the alkaline solution used in the alkaline washing operation is preferably 3-10%, for example: 5%; Wherein, in step S4, the water washing operation is preferably to adjust the pH value of the object to be washed to 6-8; Wherein, in step S4, the water washing operation is preferably performed using pure water; Preferably, in step S4, the drying operation is performed under one of air, nitrogen and argon atmospheres, for example: air; Preferably, in step S4, the drying temperature is 100-170°C, more preferably 100-150°C, for example 130°C; Preferably, in step S4, the drying time is preferably 2 to 5 hours, more preferably 2 to 4 hours; (10) The carbonization yield of the porous carbon microspheres is 45% to 60%, preferably 45% to 55%.

6. Porous carbon microspheres prepared by the method for preparing porous carbon microspheres according to any one of claims 1 to 5.

7. A porous carbon microsphere, characterized in that: The average pore size of the porous carbon microspheres is 2-6 nm; the mesoporosity of the porous carbon microspheres is 40%-80%; the mesopore volume of the porous carbon microspheres is 0.2-0.8 cm 3 / g; the micropore volume of the porous carbon microspheres is 0.3~0.6 cm 3 / g; the compressive strength of the porous carbon microspheres is 4.8~8.0 Gpa.

8. The porous carbon microspheres according to claim 7, characterized in that: The average pore size of the porous carbon microspheres is 2-4 nm; the mesoporosity of the porous carbon microspheres is 48%-65%; the mesopore volume of the porous carbon microspheres is 0.3-0.6 cm 3 / g; the micropore volume of the porous carbon microspheres is 0.3~0.5 cm 3 / g; the compressive strength of the porous carbon microspheres is 5.2~7.0 Gpa; And / or, the specific surface area of ​​the porous carbon microspheres is 700-1500 m 2 / g, preferably 1000~1400 m 2 / g; the total pore volume of the porous carbon microspheres is 0.4~1.3 cm 3 / g, preferably 0.7~1.0cm 3 / g; And / or, the D50 of the porous carbon microspheres is less than 9 μm, preferably 6.7-8.3 μm; the D90 of the porous carbon microspheres is less than 17 μm, preferably 14.2-16.8 μm.

9. A silicon-carbon composite material, characterized in that: It comprises the porous carbon microspheres as claimed in claim 6 or 7 and silicon, wherein the silicon is enriched inside the pores of the porous carbon microspheres; The content of silicon in the silicon-carbon composite material is preferably 45% to 60%; The silicon-carbon composite material is preferably prepared by depositing the silicon in the porous carbon microspheres by chemical vapor deposition.

10. Use of the silicon-carbon composite material as claimed in claim 9 as an electrode material in a lithium-ion battery.

Citation Information

Patent Citations

  • Preparation method of silicon-carbon composite material, silicon-carbon composite material and application of silicon-carbon composite material

    CN116314734A

  • A high performance asphalt-based porous carbon material and preparation method thereof

    CN118206115B

  • Lithium ion battery carbon microsphere negative electrode material and preparation method thereof

    CN103107319A

  • Preparation method of nitrogen-doped CA / PAN-based carbon microsphere electrode material

    CN105869925A

  • High-purity and high-conductivity porous carbon and preparation method thereof

    CN112299410A

Cited By

  • Millimeter-scale uniformly-distributed honeycomb-shaped hole carbon sphere as well as preparation method and application thereof

    CN120483069A

  • Spherical porous carbon, silicon-carbon composite material, preparation method and application of spherical porous carbon and silicon-carbon composite material, and battery

    CN120483148A